Drought and disaster in a revolutionary age: colonial Antigua during the American Independence War - Berland, Alexander Jorge; Endfield, Georgina H. (White Horse Press, 2018)
The American War of Independence (1775-1783) spelled crisis for the British West Indies. Trade embargos between rebelling and loyal territories, losses to American pirates and hostilities with other European states left the Crown’s tropical Atlantic colonies short of the imported supplies that normally sustained their populations and commerce. Historians have studied the dynamics and consequences of these developments in considerable detail, at both regional and local scales, but have tended to focus on economic, social and political dimensions of the subject matter. Although some investigations have highlighted that climate variability compounded agricultural and subsistence problems in certain locations, the role of climate has rarely been subject to the same level of scrutiny. The present paper addresses this theme by focusing on the Lesser Antillean island of Antigua and the severe drought which gripped the colony during the war period. Through extensive analysis of original, largely unpublished archival sources, the implications of deficient rainfall for human livelihoods, fiscal stability and governmental crisis management are examined. By supplementing findings with evidence from other episodes of warfare which coincided with extreme climate phenomena in the late 1700s and early 1800s, it is argued that successive years of drought were pivotal in defining the severe human and economic losses sustained in Antigua during the American independence conflict. The critical agency of this weather event must, however, be understood as the product of its dynamic interaction with the precarious backdrop of a colonial regime under profound socio-economic and geopolitical stress.